Biomass-derived activated carbon catalysts for the direct dimethyl ether synthesis from syngas - Palomo-Jiménez, José; Rodríguez-Cano, Miguel Ángel; Rodríguez-Mirasol, José; Cordero-Alcántara, Tomás (Elsevier, 2024)
The direct DME synthesis from syngas was studied by using activated carbon-based bifunctional catalytic beds. Two kinds of activated carbons, prepared by physical (by CO2 partial gasification) and chemical (with phosphoric acid) activation of olive stones, were used as supports for the preparation of the catalysts. The chemically activated carbon presented a considerable amount of thermally and chemically stable surface phosphorus complexes, which played an important role on the catalytic performance of the prepared catalysts. A Zr-loaded P-containing activated carbon presented a relatively high activity, selectivity and stability for the production of DME from methanol and was used as methanol dehydration catalyst. On the other hand, Cu-Zn was loaded on both P-containing and P-free activated carbon supports for the preparation of methanol synthesis catalysts. The presence of surface-phosphorus on the carbon support resulted in a strong metal-support interaction, hindering the catalytic activity for the hydrogenation of CO to methanol. However, the catalyst that did not contain phosphorus showed noticeable activity for this reaction. The physical mixing of the methanol synthesis and methanol dehydration catalysts resulted in the preparation of carbon-based bifunctional catalytic beds, which performed very efficiently in the direct DME synthesis from syngas in a fixed-bed reactor. Different mass ratios of the individual (metallic and acid) catalysts were studied. An acid/metallic catalyst mass ratio of 2 provided the catalytic bed with enough acid sites to promote methanol dehydration to its maximum extent and make the overall product distribution controlled by the methanol synthesis reaction on the metallic phase.
Keywords: Catalizadores; Biomasa; Carbón activado; Gas de síntesis; Syngas; Activated carbon; Biomass derived; Catalysts